Media and peer culture: Young people sharing norms and collective identities with and through media - LIM, Sun Sun (Institutional Knowledge at Singapore Management University, 2022)
When young people interact, they absorb the peer culture that underpins and sustains their relationships with each other. Peer culture encompasses norms and conventions, shared interests and activities, and the unique modes of communication deployed in the afore-mentioned elements. The ways in which young people integrate their media consumption into their peer culture is the focus of this chapter. Specifically, it examines how young people incorporate media content into their peer interactions and appropriate a variety of communication platforms to socialize with their peers, thus generating distinctive traits, norms, practices, codes and shared identities that make up their unique peer culture(s). It covers the three salient ways in which young people around the world today interact with one another: face-to-face, via the mobile phone and over the Internet’s myriad communication channels. The chapter then provides a closer examination of youth subcultures that are media-based and media-facilitated.